Wear performance of calcium carbonate-containing knee spacers - Müller, Ulrike; Kretzer, Jan Philippe (Materials, 2017)
Articulating spacers should be wear-resistant and load-bearing to avoid prolonged immobilization of the patient and to reduce morbidity. However, due to the articulation of both components, a release of cement wear particles is to be expected. The aim of this study was to investigate the wear performance of a new spacer cement that contains calcium carbonate as a radio-opaque substance, in comparison to an established barium sulphate-containing spacer material, and also to characterize the amount, morphology, and size distributions of the released cement particles in detail. Force-controlled simulation was carried out on an AMTI knee simulator. The test parameters were in accordance with the standard ISO 14243-1 with a 50% reduced axial force. Tests were run for 500,000 cycles at a frequency of 1 Hz. For wear analysis, photographic documentation of the wear scars, gravimetric wear measurements and wear particle analysis were performed. The barium sulphate spacer material showed a total articular wear of 375.53 ± 161.22 mg. For the calcium carbonate-containing cement, reduced articular wear of 136.32 ± 37.58 mg was determined. Isolated cement wear particles of the barium sulphate-containing cement had a diameter of 0.429 ± 0.224 μm and were significantly larger compared to the calcium carbonate-containing cement (0.380 ± 0.216 μm, p = 0.02). The calcium carbonate-containing cement showed better wear performance in terms of gravimetric wear and particle release. Thus, calcium carbonate seems to be a promising material as a radio-opaque substrate in cement spacers.